High Accuracy Resonator Spectroscopy of Atmospheric Gases at Millimetre and Submillimetre Waves - Tretyakov, M. Yu (Cambridge Scholars Publisher, 2022)
This book is devoted to the most efficient method of obtaining spectroscopic parameters characterising the absorption of microwave radiation by the Earth's atmosphere. It explores why this field of science is interesting and important for humanity, and details the basics of gas phase molecular spectroscopy. The book also shows the advantages of the resonator spectroscopy technique for quantitative molecular analysis, and reviews the best-known investigations of diagnostic atmospheric lines and the continuum in the millimetre and submillimetre-wave range. It will appeal to a wide range of speci.